Authentication securing methods for mobile identity: issues, solutions and challenges - Ahmad Zukarnain, Zuriati; Muneer, Amgad; Ab Aziz, Mohd Khairulanuar (MDPI, 2022)
Smartphone devices have become an essential part of our daily activities for performing various essential applications containing very confidential information. For this reason, the security of the device and the transactions is required to ensure that the transactions are performed legally. Most regular mobile users’ authentication methods used are passwords and short messages. However, numerous security vulnerabilities are inherent in various authentication schemes. Fingerprint identification and face recognition technology sparked a massive wave of adoption a few years back. The international mobile equipment identity (IMEI) and identity-based public key cryptography (ID-based PKC) have also become widely used options. More complex methods have been introduced, such as the management flow that combines transaction key creation, encryption, and decryption in processing users’ personal information and biometric features. There is also a combination of multiple user-based authentications, such as user’s trip routes initialization with the coordinates of home and office to set template trajectories and stay points for authentication. Therefore, this research aimed to identify the issues with the available authentication methods and the best authentication solution while overcoming the challenges.